Разработка современных систем цифровой оптической микроскопии - Аврунін, О. Г.; Носова, Т. В.; Масловский, С. Ю.; Калашник, Ю. М. (ХНУРЭ, 2011)
The work is devoted to design the modern digital optical microscopy systems. The problems of digital processing for histological images are described. The root principles of design, main issues of imaging processing and structure of the system for automatical сito histological research are proposed. Main medical–technical requirements for proposed system are considered and described.
Keywords: медицинская техника; гистологические данные; цитологические данные